Media ecology and hashtag activism: #Kaleidoscope - Crandall, Heather and Cunningham, Carolyn M. (Explorations in Media Ecology, 2016)
Abstract A new form of social change through social media is hasthag activism, in which activists draw attention to a specific cause by using a metadata tag, such as #BlackLivesMatter. This new mechanism for social change in our new media environment is questionable, and there is little understanding of what this type of activism creates. Media ecology offers insight into the possible consequences of engagement with hashtag activism and proposes ways we can understand how it alters our consciousness and behaviour. Using the metaphor of a kaleidoscope, we explore what hashtag activism offers, its multi-layered beauty as well as the dark side of this new media form. We examine how hashtag activism furthers (and doesn’t) democratic communication and participation and offer some directions for future research into these online forms of resistance.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9lbWUuMTUuMS4yMV8x